The Message of Peace In The Song Atouna el Toufoule By Remi Bandali: A Semiotic Study Of Ferdinand De Saussure - Salma Nuraeni; Jarot Wahyudi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Messages of peace can be effectively conveyed through various artistic expressions, including songs. This study examines the message of peace contained in the song Atouna El Toufoule by Remi Bandali, which reflects the suffering of Palestinian children as victims of war and conflict. The research is motivated by the ongoing global concern over the Israeli–Palestinian conflict, which threatens peace and security, especially for vulnerable groups such as children. Using a qualitative method, this study applies Ferdinand de Saussure’s semiotic theory to analyze the song lyrics and video imagery. The analysis focuses on signifiers and signifieds to reveal how linguistic and visual elements construct meaning. The findings show that Atouna El Toufoule contains a strong message of peace, emphasizing children’s longing for safety, freedom, and a return to their childhood. Repeated lyrics such as “Give us peace” and “Give us childhood” symbolize an urgent plea for justice, security, and dignity. Visual representations in the music video further reinforce these meanings, depicting destroyed homes, children’s tears, and dark skies as symbols of loss and oppression. The study concludes that the song is not only an artistic expression but also a powerful medium of resistance, awareness, and humanitarian advocacy. It represents a universal call for peace inspired by Islamic values of love, justice, and harmony